1979
DOI: 10.1126/science.203.4378.330
|View full text |Cite
|
Sign up to set email alerts
|

Fission Power: An Evolutionary Strategy

Abstract: Motivated by concerns about the difficulty of safeguarding the large flows of plutonium in a breeder reactor fuel cycle, we explore the resource and economic implications of a strategy in which there is no nuclear weapons-usable material in fresh reactor fuel. The strategy involves the deployment of already developed types of advanced converter reactors which, unlike the breeder, can be operated effectively on proliferation-resistant once-through fuel cycles. Advanced converter reactors could be much more uran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The energy crisis is likely to be with us for a long time, and even the most enthusiastic proponents of the present form of nuclear power must realize that providing 50% or more of our energy requirements by nuclear means would involve a tremendous proliferation of nuclear reactors and their attendant industries (reprocessing plants, etc.). This assumes that sufficient nuclear fuel would be available and the system would remain economically feasible (see Koslow 1977;Feiveson et al 1979). This vast increase in the nuclear industry would not only increase the risk of serious accidents, but would also create a serious and costly problem of waste management.…”
Section: Discussionmentioning
confidence: 98%
“…The energy crisis is likely to be with us for a long time, and even the most enthusiastic proponents of the present form of nuclear power must realize that providing 50% or more of our energy requirements by nuclear means would involve a tremendous proliferation of nuclear reactors and their attendant industries (reprocessing plants, etc.). This assumes that sufficient nuclear fuel would be available and the system would remain economically feasible (see Koslow 1977;Feiveson et al 1979). This vast increase in the nuclear industry would not only increase the risk of serious accidents, but would also create a serious and costly problem of waste management.…”
Section: Discussionmentioning
confidence: 98%
“…Economics was an important cause for disenchantment with breeders. Several studies have shown that electricity from breeder reactors is expensive in Ramana comparison with that from light water reactors that dominate the worldÕs nuclear capacity (Bunn et al, 2005;Chow, 1995;Cochran, 1974;Feiveson et al, 1979). In contrast, the Department of Atomic Energy has long claimed that the cost of electricity from breeder reactors is comparable to that of electricity from a pressurized heavy water reactor, the reactor type that accounts for the largest share of nuclear generation in the country (Bhoje, 2003;Paranjpe, 1991).…”
Section: Reactor Case Studiesmentioning
confidence: 99%
“…Our approach makes use of a fusion driven fission engine that combines the best aspects of nuclear fusion and fission, termed Laser Inertial Fusion Energy (LIFE), and consists of an ICF neutron source (typically 1 − 2 × 10 20 n/sec) surrounded by a spherical subcritical fission blanket. Fusion-fission hybrid concepts have been studied in the past with encouraging results [12,13,14]. Andrei Sakharov originally discussed the concept of fusion driven fission systems in the 1950's [15].…”
Section: Introductionmentioning
confidence: 99%